A novel selective androgen receptor modulator (SARM) MK-4541 exerts anti-androgenic activity in the prostate cancer xenograft R–3327G and anabolic activity on skeletal muscle mass & function in castrated mice. Issue 163 (October 2016) - Chisamore, Michael J.; Gentile, Michael A.; Dillon, Gregory Michael; Baran, Matthew; Gambone, Carlo; Riley, Sean; Schmidt, Azriel; Flores, Osvaldo; Wilkinson, Hilary; Alves, Stephen E.
Highlights: MK-4541 is a unique SARM providing anti-androgen effects on the prostate. MK-4541 is a unique SARM impacting CNS function by restoring general activity. MK-4541 is a unique SARM providing protective effects on skeletal muscle. Abstract: The androgen receptor (AR) is a member of the nuclear hormone receptor super family of transcription factors. Androgens play an essential role in the development, growth, and maintenance of male sex organs, as well as the musculoskeletal and central nervous systems. Yet with advancing age, androgens can drive the onset of prostate cancer, the second leading cause of cancer death in males within the United States. Androgen deprivation therapy (ADT) by pharmacologic and/or surgical castration induces apoptosis of prostate cells and subsequent shrinkage of the prostate and prostate tumors. However, ADT is associated with significant musculoskeletal and behavioral adverse effects. The unique pharmacological activity of selective androgen receptor modulator (SARM) MK-4541 recently has been reported as an AR antagonist with 5α-reductase inhibitor function. The molecule inhibits proliferation and induces apoptosis in AR positive, androgen dependent prostate cancer cells. Importantly, MK-4541 inhibited androgen-dependent prostate growth in male rats yet maintained lean body mass and bone formation following ovariectomy in female rats. In the present study, we evaluated the effects of SARM MK-4541 in the androgen-dependent Dunning R3327-G prostate carcinoma xenograft mouse model as well as on skeletal muscle mass and function, and AR-regulated behavior in mice. MK-4541 significantly inhibited the growth of R3327-G prostate tumors, exhibited anti-androgen effects on the seminal vesicles, reduced plasma testosterone concentrations in intact males, and inhibited Ki67 expression. MK-4541 treated xenografts appeared similar to xenografts in castrated mice. Importantly, we demonstrate that MK-4541 exhibited anabolic activity in androgen deficient conditions, increasing lean body mass and muscle function in adult castrated mice. Moreover, MK-4541 treatment restored general activity levels in castrated mice. Thus, MK-4541 exhibits an optimum profile as an adjuvant therapy to ADT which may provide potent anti-androgenic activity at the prostate yet protective activity on skeletal muscle and behavior in patients.